2022
DOI: 10.1155/2022/7621658
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-Based Care Can Improve Treatment Compliance and Quality of Life of Patients with Acute Pancreatitis

Abstract: Acute pancreatitis represents a disease characterized by acute necro-inflammatory changes in the pancreas, which is histologically characterized by destruction of alveolar cells. We aim to explore whether evidence-based care can improve treatment compliance and quality of life of patients with acute pancreatitis. The changes of hemoglobin (HGB), serum pre-albumin (PAB), and serum albumin (ALB) before and after care were observed, as well as the incidence of complications after care, total effective rate after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…erefore, electrolytes and blood glucose need direct control. Various studies have also shown that all pharmacological efforts to reduce pancreatic secretion, including anticholinergic drugs, somatostatin analogs, antacids, and aprotinin, have no significant benefit [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, electrolytes and blood glucose need direct control. Various studies have also shown that all pharmacological efforts to reduce pancreatic secretion, including anticholinergic drugs, somatostatin analogs, antacids, and aprotinin, have no significant benefit [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, long-term medication, loss of treatment confidence, a negative psychological state, and low treatment compliance at home care are associated with poor treatment outcomes and reduced QoL. 13,14 In this context, the hospital-community-family nursing model has emerged. The hospital-community-family linkage continuum of nursing care is an intervention model that effectively combines nursing at hospital, community and family, which extends the specialized care services from the hospital to the family, provides continuous and systematic care services, multi-level psychological, technical and professional information and care measures.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled "Evidence-Based Care Can Improve Treatment Compliance and Quality of Life of Patients with Acute Pancreatitis" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Evidence-Based Care Can Improve Treatment Compliance and Quality of Life of Patients with Acute Pancreatitis” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%